The first-order structural transition in NiO at high pressure - Gavriliuk, Alexander G.; Struzhkin, Viktor V.; Ivanova, Anna G.; Prakapenka, Vitali B.; Mironovich, Anna A.; Aksenov, Sergey N.; Troyan, Ivan A.; Morgenroth, Wolfgang (Communications physics, 2023)
Insulator-metal transition in NiO and concomitant collapse of spin and magnetism in the material are important subjects in studies of strong electronic correlations and as such they generate multiple theoretical and experimental efforts aimed at understanding the complicated physics of strongly correlated electronic systems. We report here the iso-structural transition in NiO accompanying the previously observed by us transition to the metallic state. These findings resolve some experimental controversies regarding the transition. We also discuss the latest theoretical results in detail and show that our data confirm some recent theoretical models. Given the simplicity of the material and its fundamental importance to the understanding of strongly correlated electronic systems, our findings should stimulate further experimental and theoretical efforts to understand this prototype Mott insulator. The physics of NiO under applied pressure has long been debated and the material has been a key contributor to our understanding of Mott insulators and strongly correlated materials more generally. Here, the authors perform high-pressure X-ray diffraction measurements reporting a pressure-induced structural phase transition for NiO, which they suggest is linked with the metal-insulator transition of this system.